Digital Transformation and XAI in Healthcare - Uysal, Ilhan; Rodríguez Aguilar, Román; Abed Alzubi, Jafar Ahmad; Bilen, Mehmet (CRC Press, 2025)
This book explores the pivotal role of explainable artificial intelligence (XAI) in driving digital transformation within the healthcare sector, providing comprehensive insights into its applications, ethical and legal considerations, technological requirements, and future trends. Digital Transformation and XAI in Healthcare delves into the fundamental role of XAI in transforming healthcare, addressing critical issues such as data security, ethical considerations, and the integration of XAI into existing healthcare infrastructures. By offering a comprehensive overview of technological tools, infrastructure requirements, and legal frameworks, this book equips healthcare professionals with the knowledge to navigate the complexities of XAI applications. The book explores the future of healthcare education and the pivotal role of XAI in training the next generation of healthcare professionals. It discusses how XAI can enhance learning experiences and provide more personalized education, ensuring that future clinicians are well equipped to utilize advanced AI technologies. It also delves into the technological tools and infrastructure required for implementing XAI, as well as data management and privacy concerns. The exploration of global collaborations and innovative projects highlights the book's unique perspective on the international impact of XAI in healthcare. Intended for healthcare professionals, researchers, and students, this book will provide valuable insights into the future of healthcare technology. Readers will be equipped with the knowledge to harness the power of XAI, ensuring that AI systems are not only accurate but also transparent, trustworthy, and ethically sound. ©The authors ©CRC Press.
1. Explainable Artificial Intelligence and Digital Transformation in Healthcare / Fatma Gul Altin, Ilhan Uysal -- 2. Legal and Ethical Issues in Healthcare / Tulay Turan -- 3. Sectoral Applications of XAI in Healthcare / Manjeet Singh, Surbhi Gupta -- 4. Technology and Infrastructure for XAI in Healthcare / Osama Burak Elhalid, Ali Hakan Isik -- 5.Data Management and Privacy / Mahreen Fatima, Arooj Fatima, Amjad Islam Aqib, Ayesha Tariq, Ieman Tariq -- 6. Decision Support Systems in Healthcare : Applications, Benefits, Challenges, and Future Trends / R. S. M. Lakshmi Patibandla -- 7. Healthcare Educatıon and XAI : Future Directıons / Giray Kolcu, Mukadder Inci Baser Kolcu -- 8. Multinational Collaborations and Innovation / Ilhan Uysal, Surbhi Gupta -- 9. Investigation on Deployment of XAI in Healthcare through Augmented Analytics and Augmented Artificial Intelligence / Moushumi Barman, Abhijit Bora -- 10. Generative Artificial Intelligence and Generative Adversarial Networks (GAN) / Ayhan Arisoy -- 11. Applications of Big Data Analytics in Healthcare : Insights from Medical Tourism / ByZeynep Dereli -- 12. Data Management and Integration / José Antonio Marmolejo Saucedo, Utku Kose, Jafar Ahmad Abed Alzubi, Ilhan Uysal, Gamze Kose -- 13. Revolutionizing Medical Care : The Role of Metaverse and NFTs in Modern Healthcare / V. S. Devi Priya, Sumathi Doraikannan, V. Vinitha, P. Ranjima, Mehmet Bilen -- 14. The Future of XAI and Digital Transformation in Healthcare / Gokhan Turan -- 15.Ensuring Patient Autonomy and Informed Decision-Making in AI-Driven Healthcare / Safa Kaymakci, Bekir Yitik.
Keywords: Medical informatics; Artificial intelligence -- Medical applications; Bioscience; Computer Science; Engineering & Technology; Health and Social Care; Medicine; Dentistry; Nursing & Allied Health